The cornerstone of excellence: quality procedures in the faculty of pharmacy - Ismail, Farhana Fakhira; Abdullah, Zafirah Liyana (Faculty of Pharmacy, 2025)
At the Faculty of Pharmacy, the Manual Kualiti acts as the primary reference for procedures that have been carefully developed to ensure accountability, consistency, and compliance with both university standards and professional requirements. Procedures and their compliance serve as a cornerstone of the smooth and effective functioning of an academic institution. These procedures cover a wide range of administrative and academic matters, providing clear and actionable guidance for all faculty members.